Time-dependent Seismic Performance Assessment of Corroded Reinforced Concrete Frames - Ghanooni-Bagha, Mohammad; Zarei, Sajad; Savoj, Hamid Reza; Shayanfar, Mohsen Ali (Periodica Polytechnica Civil Engineering, 2019)
In this study, effects of reinforcement corrosion such as reinforcement cross section reduction, steel yield strength and concrete compressive strength reduction on RC member capacity decrease are studied. Next, a two-dimensional reinforced concrete moment resistant frame is modeled to evaluate the effects of moderate and severe intensity corrosion on moment-curvature behavior of elements and structure seismic response under nonlinear analysis. Structure capacity curves in push-over analysis and failure curves resulted from IDA for both the structure without and with corrosion are obtained and the effects of reinforcement’s corrosion on the reinforced concrete frame seismic performance are determined through comparing the results. The results revealed that in terms of amount, place and type of corrosion in the reinforced concrete frame, value of the reduction resisting moment of elements is different. Furthermore, the outcomes of nonlinear analyses showed that the capacity of structure is reduced and its seismic performance level is changed as a result of corrosion.